2015
DOI: 10.1007/s12311-015-0713-5
|View full text |Cite
|
Sign up to set email alerts
|

Anodal Direct Current Stimulation of the Cerebellum Reduces Cerebellar Brain Inhibition but Does Not Influence Afferent Input from the Hand or Face in Healthy Adults

Abstract: Anodal DCS reduced CBI but did not change SAI or TRs in healthy adults. These results require confirmation in individuals with neurological impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 61 publications
(94 reference statements)
4
23
0
Order By: Relevance
“…Anodal tDCS Cb has been reported to have no after-effect on SAI when tested with PA currents at rest in healthy volunteers [17] , [23] . However, abnormal SAI has been found in patients with cerebellar degeneration [12] , and also in patients with Alzheimer's disease where it has been shown to be partially dependent on cerebellar function [13] .…”
Section: Discussionmentioning
confidence: 96%
“…Anodal tDCS Cb has been reported to have no after-effect on SAI when tested with PA currents at rest in healthy volunteers [17] , [23] . However, abnormal SAI has been found in patients with cerebellar degeneration [12] , and also in patients with Alzheimer's disease where it has been shown to be partially dependent on cerebellar function [13] .…”
Section: Discussionmentioning
confidence: 96%
“…For example, one study demonstrates that anodal tDCS to the right cerebellum increases the inhibitory effect to the primary motor cortex while cathodal tDCS to the right cerebellum reduces this effect [ 15 ]. In contrast, another study in this field reports that anodal c-tDCS may reduce the inhibitory effect to the primary motor cortex [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means anodal c-tDCS would decrease prefrontal cortex activity whereas cathodal c-tDCS would increase prefrontal cortex activity. However, literature regarding the efficacy of c-tDCS is inconsistent, for example, a study by Doeltgen et al [ 18 ] reported that anodal c-tDCS may reduce the inhibitory effect on the primary motor cortex. Also, a study focusing on language functioning [ 19 ] found that both anodal and cathodal c-tDCS enhanced the performance on a phonemic fluency task.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we did not include a measure of cerebellar output, such as CBI, because CBI has not been yet been demonstrated to exist in UT cortical representations. However, TBS has consistently influenced hand muscle CBI [32,34,41], as has cerebellar direct current stimulation when the anode is placed over the lateral cerebellum [42,76]. Furthermore, PET scanning demonstrated robust metabolic effects in both cerebellar cortex and deep cerebellar nuclei following cTBS applied to the lateral cerebellum [31].…”
Section: Discussionmentioning
confidence: 99%